Mayo Clinic Guide to a Healthy Pregnancy - Wick, Myra; Mayo Clinic ([Rochester, Minnesota] : Mayo Clinic Press, 2024)
Pregnancy can be an adventure -- full of thrilling moments, unknowns, decisions and joy. Mayo Clinic Guide to a Healthy Pregnancy is the ultimate guidebook for navigating the road to parenthood, with everything you need to know along the way to help you have a healthy pregnancy and baby. This inclusive, updated manual is packed with research-backed advice for every part of the journey, from conception to postpartum and the newborn weeks. Inside you'll find the latest expertise from Myra Wick, M.D., Ph.D., a mom of four -- along with contributions from many other pregnancy specialists at Mayo Clinic. Month-by-month chapters walk you through the physical changes you can expect as your baby grows and develops, milestones to watch for (feel those kicks!), and key steps in prenatal care. You'll also learn about diet and lifestyle choices to give you and your baby a healthy start, exercises to stay active and strong, and treatments that can actually help with morning sickness.
Includes bibliographic references and index.
Keywords: Pregnancy; Prenatal care; Childbirth; Prenatal Care; Pregnancy; Gynecology and obstetrics